Biophysical controls on seasonal changes in the structure, growth, and grazing of the size-fractionated phytoplankton community in the northern South China Sea - Y. Dong; Y. Dong; Q. P. Li; Q. P. Li; Q. P. Li; Z. Wu; Z. Wu; Y. Shuai; Y. Shuai; Z. Liu; Z. Liu; Z. Ge; et al. (Biogeosciences, 2021)
The size-fractionated phytoplankton growth and microzooplankton grazing are crucial for the temporal change of community size structure, regulating not only trophic transfer but also the carbon cycle of the ocean. However, the size-dependent growth and grazing dynamics on a monthly or an annual basis are less addressed in the coastal ocean. In this paper, the seasonal responses of the size-fractionated phytoplankton growth and grazing to environmental change were examined over 1 year at a coastal site of the northern South China Sea. We found a nanophytoplankton-dominated community with strong seasonal variations in all size classes. Phytoplankton community growth rate was positively correlated to nutrients, with community grazing rate correlating to the total chlorophyll a at the station, reflecting a combined bottom-up and topdown effect on phytoplankton population dynamics. Further analyses suggested that the specific growth rate of microphytoplankton was significantly influenced by phosphate, and that of nanophytoplankton was influenced by light, although picophytoplankton growth was controlled by both nitrate and temperature. In addition, the specific grazing rate of nanophytoplankton was well correlated to phytoplankton standing stock, while that of micro- and pico-compartments was negatively influenced by ciliate abundance and salinity. Finally, a lower grazing impact for micro-cells (38 %) than nano- and pico-cells (72 % and 60 %, respectively) may support size-selective grazing of microzooplankton on small cells at this eutrophic system.